Impact of spatially-variable soil thickness and texture on simulated hydrologic conditions in a semiarid watershed in northwest Mexico - Luis A. Méndez-Barroso; Enrique R. Vivoni; Giuseppe Mascaro (Revista Mexicana de Ciencias Geológicas)
Soil depth and texture exert strong controls on the spatial distribution of water and energy fluxes and states in semiarid watersheds. As a result, realistic representations of the spatial soil characteristics within watersheds are important for the improvement of process-based distributed hydrologic modeling applications. In this study, we evaluated the effects of combinations of soil thickness and soil texture products with varying spatial distributions to assess their effects on the simulated hydrologic response in the semiarid Sierra Los Locos watershed in Sonora, Mexico. The main findings of the hydrological simulations show that soil texture exerted a strong control on evapotranspiration and soil moisture patterns, while soil thickness was directly related with the magnitude and range of the simulated values. Furthermore, soil texture patterns were an important factor controlling the spatial and temporal persistence of soil moisture which is highly evident during the transition from dry to wet conditions in the North American monsoon region. Once vegetation cover increases in the watershed in response to seasonal rainfall, the influence of soil texture decreases for determining the spatial distribution of the simulated hydrologic response and soil thickness becomes more important. Spatially-variable soil thickness tends to create soil depressions that store and transmit subsurface water, leading to large spatial variations in soil moisture, evapotranspiration and runoff generation. The results of this study highlight the sensitivity of estimated water fluxes and states with respect to the spatial distribution of soil depth and texture as obtained in a distributed hydrologic model representative of modern approaches. Finally, this research work offers insight into the importance of field studies and remote sensing approaches to better characterize these watershed properties.